DISTINGUISHING MOTION AND WORK IN MECHANICS AND ENGINEERING THERMODYNAMICS (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
To fully appreciate Bejan’s engineering thermodynamics, it is important to distinguish it from the Clausius, Boltzmann, Gibbs (CBG) mechanical rendering of thermodynamics. Concepts of motion and work occur in both formulations but have different meanings. The aim here will be to distinguish Bejan’s concepts from CBG’s classical mechanical exposition. The latter reason is classical Newtonian mechanics. Focusing on motion and work also allows us to trace the historical antecedents of Bejan’s thermodynamics, including the contributions of Lazare and Sadi Carnot.
Keywords: Parallelogram of forces; Cyclic oscillation; Thermodynamic motion and work; Mechanical motion and work